1999
DOI: 10.1046/j.1529-8817.1999.3540682.x
|View full text |Cite
|
Sign up to set email alerts
|

SYNTHESIS OF MYCOSPORINE‐LIKE AMINO ACIDS IN CHONDRUS CRISPUS (FLORIDEOPHYCEAE) AND THE CONSEQUENCES FOR SENSITIVITY TO ULTRAVIOLET B RADIATION

Abstract: The induction and protective role of the UV-absorbing compounds known as mycosporine-like amino acids (MAAs) were examined in sublittoral Chondrus crispus Stackh. transplanted for 2 weeks in the spring and summer to shallow water under three irradiance conditions: PAR (photosynthetically active radiation; 400-700 nm), PAR ؉ UVA (PAR ؉ 320-400 nm), PAR ؉ UVA ؉ UVB (PAR ؉ UVA ؉ 280-320 nm). Sublittoral thalli collected around Helgoland, North Sea, Germany, from 6 m below the mean low water of spring tides contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
14

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 50 publications
(87 reference statements)
3
54
0
14
Order By: Relevance
“…Previous research has shown that macroalgae and corals can adapt to UV-R by producing sunscreen compounds such as mycosporine-like amino acids (MAAs) which absorb strongly in the UV-R wavelengths (Dunlap et al 1986;Karsten et al 1998a,b;Franklin et al 1999). These MAAs can also be passed up to higher trophic levels through the processes of grazing and predation (Carefoot et al 1998;Carroll & Shick 1996;.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that macroalgae and corals can adapt to UV-R by producing sunscreen compounds such as mycosporine-like amino acids (MAAs) which absorb strongly in the UV-R wavelengths (Dunlap et al 1986;Karsten et al 1998a,b;Franklin et al 1999). These MAAs can also be passed up to higher trophic levels through the processes of grazing and predation (Carefoot et al 1998;Carroll & Shick 1996;.…”
Section: Introductionmentioning
confidence: 99%
“…For example, degraded D1 proteins can be excised and replaced to reinstate PS II function (Aro et al 1993;Sass et al 1997). Also, cellular compounds that absorb strongly in the UVR spectrum such as MAAs in algae (Dunlap and Shick 1998;Franklin et al 1999) and flavonoids in higher plants (Bornman and Teramura 1993) can reduce the potential damage incurred from UVR wavelengths (Roy 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This does not preclude other routes of the biosynthesis of palythine, e.g. via mycosporine-glycine (Whitehead et al 2001) or shinorine (Franklin et al 1999) in other organisms, depending on their complements of the enzymes necessary for the conversions.…”
Section: Effects Of Ammonium Enrichment On Accumulation Of Maasmentioning
confidence: 99%